Use of an Online Reading Intervention to Enhance the Basic Reading Skills of Community College Students. Issue 9 (2nd September 2019) - Bauer-Kealey, Meredyth; Mather, Nancy
ABSTRACT: Approximately two-thirds of community college students nationwide are considered to not be ready for the demands of college and are therefore required to enroll in at least one developmental education course. Unfortunately, researchers have found that enrollment in developmental classes often has adverse effects on community college students and that developmental courses are time-consuming and often result in delay or prevent the completion of a degree. With a significant number of underprepared community college students, it is important to develop effective methodologies to help students acquire the skills that they will need to succeed in college and future employment. It is also important to determine how a student's experience impacts academic progress, as well as motivation to continue in college credit courses. Unfortunately, a limited amount of research exists on the use of Computer-Assisted Instruction (CAI) in developmental reading courses at the community college level. The purpose of this study was to determine the efficacy of a computer-based reading intervention, MindPlay Virtual Reading Coach, on the reading and spelling achievement of community college students, and to explore whether or not students' perceptions and attitudes changed after participation in this program. Findings demonstrated statistically significant results in both reading and spelling, as well as an increase in reading enjoyment.